Surface-enhanced absorption by self-organized silver films with aciniform-like nanoaggregates at elevated temperatures - Kim, Sang Woo (SPRINGER, 2012)
Morphological evolution of silver nanocomposite films prepared by the wet colloidal route and surface-enhanced phenomena on aggregate nanostructures evolved during annealing were investigated. Dramatic changes in morphologies of particles and pores incurred by rearragement, coarsening, premelting, and dewetting of the silver clusters at different concentrations (i.e., mass thicknesses). At a higher mass thickness, the morphological transitions from self-organized nanoaggregates with aciniform pattern at 300 degrees C to elongated and coarsened particles with circular holes at 400 degrees C to island clusters at 500 degrees C occurred in the films. The peculiar absorption with a much redder and broader surface plasmon feature, which gone far beyond the theoretical prediction, induced by the formation of aciniform nanoaggregates embedded in the porous polymer matrix at a critical mass thickness of 9.6 nm during partial degradation of the PVP polymer and rearrangement of silver clusters at 300 degrees C. The surface-enhanced absorption was dramatically reduced by the elemination of the aggregate nanostructures and the spontaneous formation of the silver nanoisland film at the dewetting temperature of 500 degrees C.
Keywords: PLASMON RESONANCE; SENSITIVE DETECTION; GOLD NANOPARTICLES; SIZE